ATP as a Pathophysiologic Mediator of Bacteria-Host Crosstalk in the Gastrointestinal Tract - Inami, Akie (Int J Mol Sci, 2018)
Extracellular nucleotides, such as adenosine triphosphate (ATP), are released from host cells including nerve termini, immune cells, injured or dead cells, and the commensal bacteria that reside in the gut lumen. Extracellular ATP interacts with the host through purinergic receptors, and promotes intercellular and bacteria-host communication to maintain the tissue homeostasis. However, the release of massive concentrations of ATP into extracellular compartments initiates acute and chronic inflammatory responses through the activation of immunocompetent cells (e.g., T cells, macrophages, and mast cells). In this review, we focus on the functions of ATP as a pathophysiologic mediator that is required for the induction and resolution of inflammation and inter-species communication.